Factors Affecting Employee Work Productivity at the Office of Environment and Forestry in Bengkulu Province - Ria Mariani; Neri Susanti; Yanto Effendi (Penerbit Jurnal Indonesia, 2021)
Consumer satisfaction is a condition where consumer feel satisfy or dissatisfy after his want and hope toward the available menu, price, facility and service are granted. Consumers will satisfy if his want or hope is granted while he will feel dissatisfy if his want and hope is not available. The purpose of this research is to find out the influence of taste, performance quality and price toward customer’s satisfaction at Uda Denai restaurant in Bengkulu city. The sample of this research is 140 customers of Uda Denai restaurant in Bengkulu city. Data are collected by using questionnaire and analysis method which used in this research is multiple linear regression, determination test and hypothesis test. The result shows that multiple linear regression shows that there is a positive influence from taste, service quality and price toward customers’satisfaction in Uda Denai restaurant in Bengkulu city. Because the regression shows positive value, Y = 10,794+ 0,178X1 + 0,397X2 + 0,137X3 + e. Taste has significance influence toward customers’ satisfaction. Because the significance score is 0,015 smaller than 0,05. Price has significance influence toward customers’ satisfaction toward customers at Uda Denai restaurant in Bengkulu City, because significance score is 0,000 smaller than 0,05. Price has the significance influence toward customers’ satisfaction at Uda Denai restaurant because the significance score is 0,028 smaller than 0,05. Taste, service quality and price influenced together toward customers’ satisfaction. It means that earlier hypothesis is proofed (Ha is accepted). It means there’s a significance influence between taste, service quality and price toward customers’ satisfaction together with determination coefficient from R square (0,454). It means that taste, service quality and price influence the customers’ satisfaction with score 45,4% while the other (100-45,4%=54,6%) is influenced by other factors which is not observed by this research.